Correlates of Emotional and Behavioural Problems in Children with Perinatally Acquired HIV in Cape Town South Africa - Louw, Kerry-Ann (Department of Psychiatry and Mental Health, 2015)
In the antiretroviral era children perinatally infected with HIV (PHIV+) are surviving into adulthood and are at risk for emotional and behavioural problems. Few studies of these problems have been conducted in low and middle income countries (LMIC) and even fewer in sub - Saharan Africa where the burden of the HIV epidemic remains heaviest. The aims of this study were to provide a quantitative description of emotional and behavioural problems in a group of children and adolescents with perinatally acquired HIV in South Africa compared to a group of well - matched HIV - negative controls and to identify demographic, biological, cognitive and contextual correlates of emotional and behavioural problems. A cross-sectional descriptive, analytical study was conducted. Participants were recruited from community and hospital based clinics. Wi thin the HIV - infected group, children were further divided into three subgroups: PHIV+ children who had never been on antiretroviral therapy (ART naïve), PHIV+ children on ART and PHIV+ children on ART with a confirmed diagnosis of HIV - related encephalopathy (HIVE) . Emotional and behavioural problems were assessed using the Child Behaviour Checklist (CBCL). Several measures were used to assess demographic, biological, cognitive and contextual correlates of problem behaviours: socio - demographic questionnaire, clinic records, neuropsychological test battery, Family Resource Scale, Family Support Scale and Center for Epidemiologic Studies - Depression Scale. Children were compared by HIV status on demographic, cognitive and contextual variables as well as the total and subscale scores of the CBCL. Multivariate comparisons of the influence of contextual and cognitive variables on CBCL total problems was performed using a hierarchical step - wise linear regression analytic procedure. The final sample (N=108) for data analysis included 78 PHIV+ children and 30 HIV - negative children. Groups were comparable with respect to demographic and contextual variables. Cognitive performance scores were significantly lower in the PHIV+ children when compared to HIV - negative controls (p<0.001). Rates of caregiver depression were higher in both groups than the lifetime prevalence rates reported in the South African population.